Gut Microbiome Response to Sucralose and Its Potential Role in Inducing Liver Inflammation in Mice - Bian, Xiaoming; Chi, Liang; Gao, Bei; Tu, Pengcheng; Ru, Hongyu; Lu, Kun (Frontiers in Physiology, 2017)
Sucralose is the most widely used artificial sweetener and its health effects have been highly debated over the years. In particular, previous studies support that sucralose consumption could alter the gut microbiota. The gut microbiome plays a key role in host health, such as digestion and fermentation of food, development of immune cells, and regulation of the enteric nervous system. Inflammation is one of the most common physical conditions associated with the dysbiosis of the gut microbiome, which is linked to a series of human diseases, such as diabetes and obesity. The aim of this study is to investigate the structural and functional effects of sucralose on the gut microbiota and associated inflammation in the host. In this study, C57BL/6 male mice received sucralose in drinking water for six months. Difference in the gut microbiota and metabolites between controls and sucralose-treated mice was determined using 16S rRNA gene sequencing, functional gene enrichment analysis and metabolomics; Expression of inflammatory genes in tissues was determined with RT-PCR. Alterations of bacterial genera showed that sucralose affects the gut microbiota and its dynamics of development. Enrichment of bacterial genes of pro-inflammatory mediators and fecal metabolites suggest that sucralose consumption may increase the risk of developing tissue inflammation via disrupting the gut microbiota, which is consistent with elevated pro-inflammatory gene expression in liver of sucralose-treated mice. Our results highlight the role of sucralose-gut microbiome interaction in regulating host health, particularly chronic inflammation.